Analisis Uji Toksisitas Akut Logam Cu Terhadap Artemia salina dan Daphnia magna - Dedy Suprayogi; Sri Hidayati L; M.Ratodi; Farhana Fitri Ardilla (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
Water pollution can become dangerous if consumed. River could be polluted with some materials namely heavy metal of chopper (Cu). Heavy metals that are accidentally consumed by human body through the skin surface, some through the respiratory or digestive tract and then accumulate in the body over time. To make an early detection of heavy metal and water quality in water bodies, some animals or plants were used. Several types of crustaceans such as Artemia salina and Daphnia magna or commonly referred to as bio indicators. This study analyze comparison of acute toxicity test that represented by LC50 value of Cu in Artemia salina and Daphnia magna. From the research result it was found that Artemia salina and Daphnia magna gave a toxic effect with LC50 values of 11.78 ppm and 7.87 ppm, respectively.